Formação em cuidados paliativos na residência médica em medicina da família e comunidade: visão dos preceptores e residentes - Santos, Gisele dos [UNIFESP] (2017)
Introduction: Currently, Brazil lives a demographic transition in parallel to the epidemiological transition characterized by triple burden of disease. According to the World Health Organization, due to population aging and chronicity of diseases, there is a high demand for Palliative Care (PC) and to solve this, there is a proposal to implement PC in Primary Health Care (PHC) which is the pillar of Unified Health System in Brazil and one of the places of work of the Family Physician (FP). General objective: analyze the teaching of Palliative Care in residences in Family Medicine (FM) of Curitiba and the metropolitan region. Specific objectives: characterize the insertion of the Palliative Care teaching in the FM residences of Curitiba and metropolitan region; identify the pedagogical strategies used for this teaching; identify, in the view of program preceptors, the skills that have been developed during the residency in Palliative Care; assimilate the residents’ perceptions of Palliative Care competencies, developed throughout medical residency in FM. Methodology: a cross-sectional, exploratory, descriptive, qualitative / quantitative study by the triangulation of methods. The study included 04 Residency Programs in Family Medicine, two of Curitiba and two in the metropolitan region. We interviewed 06 preceptors and applied a questionnaire to 43 residents (89.53% of residents). A semi-structured interview with preceptors was carried out in order to identify if there is PC teaching, PC competencies developed, strategies, teaching and learning spaces used. Residents were given a questionnaire consisting of closed-ended questions (to characterize the subjects of the research and identify PC themes suggested by the residents) an open-ended question (to identify if there is PC teaching) and a kind of Likert-type scale of self-perception of competences development created by the authors and statistically validated. The analysis of the interviews / open-ended question was performed by the thematic modality content analysis, a Likert-type scale and by descriptive statistical analysis, Linear Correlation Test (r), Bar Graph and Mann-Whitney test. Results: We identified that the teaching of PC occurs in an unstructured way in the hidden curriculum and through the punctual insertion of the thematic. According to a preceptor’s perception, there is an absence of teaching and is justified by the lack of training of the preceptor, by the short time of contact with the terminal patient in the PHC and by the absence of institutional protocol. The teaching and learning spaces cited were health unit, home care and the classroom. The pedagogical strategies cited were theoretical class, clinical case discussion, directed study and simulated clinical case. Regarding the competencies developed, residents considered themselves to be in alert zones (need for medium-term intervention) “to demonstrate communication skills with the patient, with their caregivers and with their family, especially when communicating bad news” (mean 2,77), “to prepare and orient family members and patients concerning death-related providences” (mean 2.72), "management of common intercurrences in patients in palliative care and in terminal situations of chronic diseases" (mean 2.47) , "management of pressure and decubitus ulcer" (mean 2.4), “management of oncological and non-oncological pain in terminal patient (mean 2.36), "management of nutrition in the terminal patient" (mean 2.47), to know how to make an approach to grief (mean 2.92) and to know how to provide a death certificate (2.74). The only competence in which residents consider themselves to be in danger zones is to "recognize urgent situations in PC" (mean 1.65).Conclusion: PC teaching occurs throughout the Family Medicine residency in the hidden curriculum and in an unplanned way and is probably the consequence of similarities between the principles of PC and FM. Through an instrument applied to the residents, we identified the self-perception of the development of 10 competences, proposed by SBMFC. Residents consider themselves in an alert zone for nine of these competences and consider themselves in danger zone for one of them. Based on the research carried out, we suggest structuring the teaching of PC in the FM residency so that we can train professionals with full capacity to lead patients with PC needs.